Comparative organization of the claustrum: what does structure tell us about function? - Baizer, Joan S.; Sherwood, Chet C.; Noonan, Michael; Hof, Patrick R. (Frontiers in Systems Neuroscience, 2014)
The claustrum is a subcortical nucleus present in all placental mammals. Many anatomical studies have shown that its inputs are predominantly from the cerebral cortex and its outputs are back to the cortex. This connectivity thus suggests that the claustrum serves to amplify or facilitate information processing in the cerebral cortex. The size and the complexity of the cerebral cortex change dramatically over evolution. Rodents are lissencephalic, with few cortical areas, while many primates have a greatly expanded cortex and many cortical areas. This evolutionary diversity in the cerebral cortex raises several questions about the claustrum. Does its volume expand in coordination with the expansion of cortex and does it acquire new functions related to the new cortical functions? We have examined the organization of the claustrum in animals with large brains, including great apes and cetaceans. Our data suggest that the claustrum is not always a continuous structure. In monkeys and gorillas there are a few isolated islands of cells near the main body of the nucleus. In cetaceans, however, there are many isolated cell islands. These data suggest constraints on the possible function of the claustrum. Some authors propose that the claustrum has a more global role in perception or consciousness that requires intraclaustral integration of information. These theories postulate mechanisms like gap junctions between claustral cells or a “syncytium” to mediate intraclaustral processing. The presence of discontinuities in the structure of the claustrum, present but minimal in primates, but dramatically clear in cetaceans, argues against the proposed mechanisms of intraclaustral processing of information. The best interpretation of function, then, is that each functional subdivision of the claustrum simply contributes to the function of its cortical partner.